The Distinction between Law and Social Norm and the Deprivation of Freedom: Satre’s Materialist Approach - Yang, Lefei (Transactions on Social Science, Education and Humanities Research, 2024)
This article is dedicated to examining the value of social norms by first distinct the social norms using Satre’s understanding of Serial Praxis and Group Praxis and then discussing how the social norm prevents the freedom of human beings. In Satre’s more materialist approach, human freedom is achieved only if the basic survival needs of human beings are met. At the same time, the law enables the survival of a specific group by setting limitations on certain behaviors that are harmful to group benefits; the social norm is formed to enable the dominant class’s freedom, causing inequality. Sartre, being an existentialist philosopher, demonstrates a distinct inclination towards materialism in his examination of human nature and the concept of freedom. By examining the perspective of the materialist character, people can better understand the relationship between human freedom, law, and social norms. This article analyses various theories of group behaviour and draws initial conclusions about this dilemma based on Sartre’s existentialist and materialist perspectives. The stark juxtaposition between law and social norms underscores the imperative for individuals to adhere to the law while simultaneously advocating for the eradication of social norm.